SUAREZ, Castillo. Spam poemak: Elkar argitaletxea. Donostia, 2004. 101 orrialde - Arozena, Ainhoa (EGAN, 2021)
AINHOA AROZENA. SUAREZ, Castillo. Spam poemak Elkar argitaletxea. Donostia, 2004. 101 orrialde